Respuesta :
Answer: 10
p = Pamela’s age, j = Jiris’ age
2j = p
p + j = 30
Then change things around a bit...
p + j = 30 or
30 - p = j
Then substitute
2(30 - p) = p
And solve
2(30 - p) = p
60 - 2p = p
60 = 3p
p = 20
p = Pamela’s age, j = Jiris’ age
2j = p
p + j = 30
Then change things around a bit...
p + j = 30 or
30 - p = j
Then substitute
2(30 - p) = p
And solve
2(30 - p) = p
60 - 2p = p
60 = 3p
p = 20
Answer:
Pamela is 20 years old
Jiris is 10 years old.
Step-by-step explanation:
The very first step is to identify your variables. Let's say that Pamela is 'P' and lets say Jiris is 'J.' The next step is to create an equation. 'The sum of their ages is 30' is something that we can use. So, P + J = 30. The next step is to see that Pamela is two times Jiris' age. So we can say that P = 2J. Now, in order to solve for one variable, we need to do some substitution. We know that P = 2J, so we can plug that into the first equation (P + J = 30). With this change, we now have, 2J + J = 30. With that, you combine like terms and solve for J to get an answer of J = 10. Now we can use that number and plug it into one of our previous equations, like P + J = 30. Now it is going to be P + 10 = 30. Solve for P and get an answer of 20 years old.